2015
DOI: 10.1088/0022-3727/48/48/485101
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport optimization in CZT ring-drift detectors

Abstract: Abstract. Ring-Drift design has been applied to large (7.5mm×7.5mm×2.3mm) Cadmium Zinc Telluride (CZT) devices. This low-noise, single-carrier-sensing configuration is the gold standard for spectroscopic silicon X-ray detectors. By combining the advantages of Ring-Drift with the high quantum efficiency and room-temperature operating capabilities of CZT, a simple and compact device for high-resolution spectroscopy of X-rays in the range 50-500keV can be created. Quality of CZT crystals has improved greatly in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…If carrier ranges can be measured independently, as in the case of a-Se based photoconductors, the x-ray sensitivity can be readily predicted [2]. There are several important very recent examples in which the HCE has been used, one way or another, to relate the collected charge to the carrier µτ′ products or vice versa [5][6][7][8][9][10][11][12][13][14][15][16]. It should be emphasized that in all cases there is a tacit assumption that small signal conditions are maintained i.e.…”
Section: Introduction and The Problemmentioning
confidence: 99%
“…If carrier ranges can be measured independently, as in the case of a-Se based photoconductors, the x-ray sensitivity can be readily predicted [2]. There are several important very recent examples in which the HCE has been used, one way or another, to relate the collected charge to the carrier µτ′ products or vice versa [5][6][7][8][9][10][11][12][13][14][15][16]. It should be emphasized that in all cases there is a tacit assumption that small signal conditions are maintained i.e.…”
Section: Introduction and The Problemmentioning
confidence: 99%
“…Alruhaili et al [16] studied this geometry further and demonstrated independently that even though high energy resolution was achievable with such a topology, the charge collection volume was limited to a distance of 2 mm from the collecting anode on a 8 × 8 × 2.3 mm device. Boothman et al [17] presented a comprehensive simulation study of the geometry characterised in [16]. The simulation model accurately recreated existing testing results and found optimised biasing conditions to improve charge collection extending to 2.5 mm.…”
Section: Introductionmentioning
confidence: 88%
“…The characteristic depth of the interaction was chosen such to achieve a 1/e attenuation length, corresponding to 70 µm in CZT. This energy was chosen so the results of simulations validated against existing experimental data [16,17,22].…”
Section: Injected Charge Definitionmentioning
confidence: 99%
See 2 more Smart Citations